Knockout of the gene encoding the extracellular matrix protein SNED1 results in early neonatal lethality and craniofacial malformations. Issue 2 (22nd October 2020) - Barqué, Anna; Jan, Kyleen; De La Fuente, Emanuel; Nicholas, Christina L.; Hynes, Richard O.; Naba, Alexandra
Abstract: Background: The extracellular matrix (ECM) is a fundamental component of multicellular organisms that orchestrates developmental processes and controls cell and tissue organization. We previously identified the novel ECM protein SNED1 as a promoter of breast cancer metastasis and showed that its level of expression negatively correlated with breast cancer patient survival. Here, we sought to identify the roles of SNED1 during murine development. Results: We generated two novel Sned1 knockout mouse strains and showed that Sned1 is essential since homozygous ablation of the gene led to early neonatal lethality. Phenotypic analysis of the surviving knockout mice revealed a role for SNED1 in the development of craniofacial and skeletal structures since Sned1 knockout resulted in growth defects, nasal cavity occlusion, and craniofacial malformations. Sned1 is widely expressed in embryos, notably by cell populations undergoing epithelial‐to‐mesenchymal transition, such as the neural crest cells. We further show that mice with a neural‐crest‐cell‐specific deletion of Sned1 survive, but display facial anomalies partly phenocopying the global knockout mice. Conclusions: Our results demonstrate requisite roles for SNED1 during development and neonatal survival. Importantly, the deletion of 2q37.3 in humans, a region that includes the SNED1 locus, has been associated with facial dysmorphism and short stature. Key Findings: Sned1 is an essential gene, since its homozygous ablation leads to peri‐natal lethality. Sned1 knockout results in growth defects and craniofacial malformations. Sned1 is broadly expressed in embryos, notably in cells that undergo epithelial‐to‐mesenchymal transition: such as the somitic sclerotomes and neural‐crest cells. Targeted deletion of Sned1 from neural crest cells does not affect survival but results in growth defects and facial anomalies resembling malformations observed upon the global deletion of Sned1. In humans, SNED1 is located on the long arm of chromosome 2 (2q37.3). Deletion of 2q37 in patients has been associated with facial dysmorphism. We propose that SNED1 may contribute to the phenotype of these patients and that our novel mouse models may shed light on some of the mechanisms leading to this syndrome.